Predicting Women's Life Satisfaction Through Self-Esteem, Meaning in Life, Social Connectedness, and Cognitive Emotion Regulation: A Serial Mediation Model - Horváthová, Katarína; Chen, Daniel; Ivanov, Petar (Psychology of Woman Journal, 2026)
Objective: The present study aimed to examine the direct and indirect relationships between self-esteem and life satisfaction among women and to investigate whether meaning in life, social connectedness, and cognitive emotion regulation function as serial mediators in this relationship.Methods and Materials: This cross-sectional correlational study was conducted among 701 adult women residing in Canada. Participants were recruited through online platforms, community organizations, and university-affiliated networks. Data were collected using the Rosenberg Self-Esteem Scale, Meaning in Life Questionnaire, Social Connectedness Scale–Revised, Cognitive Emotion Regulation Questionnaire, and Satisfaction with Life Scale. Descriptive statistics and Pearson correlation analyses were performed using SPSS version 29. Structural equation modeling (SEM) was conducted using AMOS version 29 to test the hypothesized serial mediation model. Model fit was evaluated using χ²/df, Comparative Fit Index (CFI), Tucker-Lewis Index (TLI), Incremental Fit Index (IFI), Goodness-of-Fit Index (GFI), Root Mean Square Error of Approximation (RMSEA), and Standardized Root Mean Square Residual (SRMR). Indirect effects were assessed using bias-corrected bootstrapping procedures with 5,000 resamples and 95% confidence intervals.Findings: The structural model demonstrated excellent fit to the data (χ²/df = 2.24, CFI = .962, TLI = .956, IFI = .963, GFI = .941, RMSEA = .042, SRMR = .038). Self-esteem significantly predicted meaning in life (β = .62, p < .001), social connectedness (β = .29, p < .001), and life satisfaction (β = .21, p < .001). Meaning in life significantly predicted social connectedness (β = .48, p < .001), cognitive emotion regulation (β = .37, p < .001), and life satisfaction (β = .39, p < .001). Social connectedness significantly predicted cognitive emotion regulation (β = .28, p < .001) and life satisfaction (β = .24, p < .001), while cognitive emotion regulation positively predicted life satisfaction (β = .18, p < .001). Bootstrap analyses revealed significant indirect effects through all mediation pathways. The serial mediation pathway from self-esteem to life satisfaction through meaning in life, social connectedness, and cognitive emotion regulation was statistically significant (β = .03, 95% CI [.01, .06]). The model explained 67% of the variance in life satisfaction.Conclusion: The findings indicate that self-esteem contributes to women’s life satisfaction both directly and indirectly through a sequence of existential, interpersonal, and emotional mechanisms. Meaning in life emerged as the strongest mediator, while social connectedness and cognitive emotion regulation further enhanced the pathway from self-esteem to life satisfaction. These results highlight the importance of integrated interventions targeting self-worth, life meaning, social relationships, and adaptive emotional regulation to promote women’s psychological well-being and overall life satisfaction.